System theory as a tool for searching for new scientific directions and problematic aspects of pharmacy in the context of social responsibility - N. O. Tkachenko; O. A. Ryzhov; B. Р. Hromovyk (Zaporozhye State Medical University, 2020)
The aim of the article is to highlight basic principles of systems theory (ST) as a tool for finding new scientific directions and substantiation of unsolved topical issues of social responsibility. That might be further used by young scientists (undergraduates, PhD students, etc.) as a basis for their scientific potential development or by interns or post-graduates in the context of continuous professional development. Materials and methods. Fundamental and applied research by domestic and foreign scientists on the selected issue, scientific and methodological publications, normative and legislative documents are employed as materials for the study. The main provisions of the ST as well as scientific methods of cognition such as analysis, synthesis, abstraction, deduction, modeling, and generalization have been used. Results. There are three basic concepts in modern science: ST, system analysis, and system approach. It is ST that allows investigating properties of systems of any nature and complexity, including the pharmaceutical system. The system approach and system analysis allow developing methods for solving problems that arise within the system, taking into account the aims and functions of the system under consideration, its structure, and all external and internal connections. Through the prism of ST, the pharmaceutical sector of the Ukrainian healthcare system can be represented as a complex open system. It performs some basic and auxiliary functions. By means of systemic approach and three methods of system research (white, black and grey boxes), considering the case study of social responsibility in pharmacy, some ideas on identifying problematic aspects have been presented and directions for further research have need outlined. Conclusion. Research work begins with the choice of a problem or research topic, taking into account the scientific direction of the whole team of researchers, whose aim is to study certain fundamental, theoretical, and experimental problems. By highlighting the main provisions of ST, we have justified its relevance for finding new research and problematic aspects of pharmacy in the context of social responsibility of young scientists, in order to develop their academic potential, as well as that of interns and post-graduates in the context of continuous professional development.